Apocynum venetum leaf extract alleviated doxorubicin-induced cardiotoxicity by regulating organic acid metabolism in gut microbiota - Zhao, Zhenxiong; Jiang, Shenglu; Fan, Qing; Xu, Kuo; Xu, Yubin; Wu, Feiqiang; Zhang, Xihong; Wang, Ting; Xia, Zhelin (Frontiers in Pharmacology, 2023)
Apocynum venetum leaf is commonly utilized for its beneficial effects in reducing blood pressure, inducing sedation, promoting diuresis, anti-aging, and cardioprotection, which also exhibit positive effects on the gut microbiota. The gut microbiota plays a role as an endocrine organ by producing bioactive metabolites that can directly or indirectly impact host physiology, specifically cardiovascular diseases. In this study, main chemical components of A. venetum leaf extract (AVLE) were identified by LC-MS, and an orally administered AVLE was employed to treat mice with doxorubicin (Dox)-induced cardiotoxicity. The results showed that AVLE contained hyperoside and oganic acids. The pharmacological findings revealed that AVLE regulated the gut microbiota, resulting in a significant increase in the levels of two organic acids, indole-3-propionic acid (IPA) and acetic acid (AA). Both IPA and AA exhibited the ability to reduce BNP, CK, and LDH levels in mice with Dox-induced cardiotoxicity. Moreover, IPA demonstrated an improvement in Dox-induced cardiac injury by inhibiting apoptosis, while AA promoted increased secretion of ghrelin through the parasympathetic nervous system, subsequently reducing cardiac fibrosis by decreasing collagen I, collagen III, and activin A. Hence, our study demonstrates that AVLE exerts a beneficial cardioprotective effect by modulating the gut microbiota, providing a potential novel target for the treatment and prevention of Dox-induced cardiotoxicity.